NewJeans: K-pop idol brand marketing strategy based on visual art - Liu Jiahao (SHS Web of Conferences)
K-pop was originally a musical style, namely Korean pop music. In recent years, it has evolved into a cultural phenomenon and formed a strong fan economy effect. Among them, NewJeans has stood out in the K-pop idol market through its unique visual art brand marketing strategy. This paper adopts the methods of literature reading and case analysis to study how visual art has a positive effect on the marketing of NewJeans, an idol brand. First, the mixed font design not only conveys the brand personality, but also enhances the visual recognition. Secondly, the retro-style MV accurately captures the aesthetic trend of the times, and at the same time applies digital art to broaden the visual possibilities. In addition, the physical goods are rich and unique, with both artistic value and practical value. Finally, the social software Phoning enhances brand affinity and fan loyalty. Finally, it is concluded that NewJeans, a brand marketing strategy based on visual art, has created a K-pop idol brand with unique artistic charm and great commercial value, which has brought new inspiration to the K-pop industry and promoted the development of related industries, highlighting the important position of idol economy in the modern cultural industry.